A cleaner deliming technology with glycine for ammonia-nitrogen reduction in leather manufacture. (1st February 2020) - Lei, Chao; Lin, Yirui; Zeng, Yunhang; Wang, Ya-nan; Yuan, Yue; Shi, Bi
Abstract: Ammonium-free deliming technology is becoming popular in the leather industry because conventional deliming with ammonium salts results in high ammonia-nitrogen (NH3 –N) concentration of tannery wastewater. However, existing ammonium-free deliming agents have inadequate buffering capacity and slow penetration rate in limed pelt. In this study, glycine with p K a of –NH3 + = 9.6 was used to delime limed cattle hides. Glycine penetrated the entire limed pelt in only 10 min because a buffer of pH 8.0–9.5 was rapidly formed by the reaction between glycine and the alkali in pelt, thereby leading to a negatively charged pelt surface (isoelectric point 6.3). The appearance and physical properties of the crust leather produced by glycine deliming process were very similar to that produced by ammonium sulfate deliming procedure. The concentration of NH3 –N in glycine deliming effluent was dramatically reduced by 99%. Moreover, glycine deliming benefitted the biological treatment of mixed tannery wastewater because of the introduction of additional carbon source to the tannery wastewater. This addition brought the ratio of total organic carbon (TOC) to total nitrogen (TN) in the wastewater much closer to the proper ratio of 10:1 for aerobic biological treatment. After aerobic biological treatment for 24 h, the concentrations of NH3 –N, TOC, and TN in the treated tannery wastewater using glycine deliming were reduced by 99%, 20%, and 53%, respectively, compared with those using ammonium sulfate deliming. Graphical abstract: Image 1 Highlights: A clean deliming technology was developed by using glycine. Glycine penetrated limed pelt as quickly as ammonium sulfate. Glycine and alkali in limed pelt formed a buffer, maintaining the float pH around 9. Glycine eliminated ammonia-nitrogen pollution in the deliming effluent. Deliming with glycine benefitted the biological treatment of tannery wastewater.